Prenatal causes of kidney diseases - Koleganova, Nadezda; Piecha, Grzegorz; Slabiak-Blaz, Natalia; Ritz, Eberhard (African Journal of Nephrology, 2012)
<span style="color: #000000; font-family: ’Merrieweather sans’, sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Deleterious environmental factors during pregnancy influence fetal development and increase therisk of cardiovascular and kidney disease in adult offspring. Undernutrition, protein restriction,excess salt, corticosteroids, or placental insufficiency disturb kidney development, causing a lowernumber of nephrons (referred to as nephron underdosing). This in turn leads to hypertension andaccelerated loss of kidney function in the adult life of the offspring. The nephron underdosingcan be observed with or without intrauterine growth restriction. A lower number of nephrons havebeen confirmed in humans with hypertension.